Implementing Computer Based Bucking Method in Producing Black pine (Pinus nigra) Logs in Bursa, Turkey - Akay, Abdullah Emin (Warsaw Univ Life Sciences-Sggw, 2016)
[No Abstract Available]
49th International Symposium on Forestry Mechanization (FORMEC) -- SEP 04-07, 2016 -- Warsaw Univ Life Sci, Warsaw, POLAND
Bilici, Ebru/0000-0003-0532-0890
Keywords: Forest products; Optimum bucking; Dynamic Programming; Black pine